2019
DOI: 10.3926/jotse.486
|View full text |Cite
|
Sign up to set email alerts
|

The design and implementation of an Arabic pronunciation application for early childhood

Abstract: Learning is not limited to a certain age group or a formal study environment.  However, the first eight years, and particularly the first three years, are most important, as the effects of the care and attention provided to the child during this period will continue throughout his or her life. A child’s early learning processes develop their educational abilities and skills, and fosters their academic achievements.Preschool can be very benefit to development and learning for children, but there are differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The haphazardness of many online designs and their failure to reach their full potential could be attributed to lack of emphasis on pedagogical underpinnings such as Bloom's taxonomy, and on technologyintegration models such as SAMAR, TIM, ADDIE, ASSURE, and etcetera. Very few studies reported on online language instructional designs based on such integrative models (Yugandhar, 2016;Aljojo et al, 2019;Mohammed, Assam and Saidi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The haphazardness of many online designs and their failure to reach their full potential could be attributed to lack of emphasis on pedagogical underpinnings such as Bloom's taxonomy, and on technologyintegration models such as SAMAR, TIM, ADDIE, ASSURE, and etcetera. Very few studies reported on online language instructional designs based on such integrative models (Yugandhar, 2016;Aljojo et al, 2019;Mohammed, Assam and Saidi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To the best of our knowledge, there is limited implementation and usage of AR technology to assist Arabic-speaking students and teachers during chemistry lessons. Most of the developed AR tools were designed to support students in other courses, such as Arabic courses [14], courses targeting impaired/disabled students [15], interactive writing courses [16], and early childhood development courses [17]. The only AR app we could find targeting Arabic speakers was developed and tested by Ewais and Troyer [18], who designed and developed an AR application to assist female elementary school students in Palestine in learning the reactions among atoms and molecules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bloom's taxonomy describes the level of skill indicators, from the stage of knowing, describing, analyzing, evaluating, creating, and critical thinking (Pentury & Anggraeni, 2019). It is known that the level of critical thinking through several stages, so the students can create ideas independently (Aljojo et al, 2019). This can be used as a benchmark in using media that fall into the HOTS, MOTS, or LOTS categories (Teimourtash & Moghaddam, 2017).…”
Section: Introductionmentioning
confidence: 99%